The 'duality' of VET in Austria : institutional competition between school and apprenticeship - Lassnigg, Lorenz [Verfasser] (My University, 2011)
"This article analyses the structure and development of Austrian apprenticeship in the context of the country's wider vocational education and training (VET) system. In doing so, it draws on official data and survey results as well as the available, related literature on historical institutionalism. It begins with an analysis of the basic structure of the VET system and shows that the modernising element in VET in Austria has always been situated in the schooling sector, whereas the structure of the apprenticeship system has changed little, remaining primarily in the traditional sectors of employment. It goes on to analyse recent developments in the apprenticeship system, revealing signs of a 'crisis' that is being resolved by establishing more institutional forms of apprenticeship. Finally, the developments in Austria are analysed with regard to more basic questions relating to the strengths and weaknesses of the apprenticeship model, indicating some quite paradoxical features and unresolved puzzles." (Autorenreferat, BIBB-Doku)
Keywords: S 1.3.1 Ausbildung im Dualen System; S 2.3 Berufsbildungspolitik; G 1.3.1.1 Ausbildungsstellenmarkt; I 2.2.1 Westeuropa; Berufsbildungssystem; Duales System; Berufsbildungspolitik; Ausbildungsstellenmarkt; Beziehung Bildungssystem Beschäftigungssystem; Österreich